Comparative analysis of the stability features of human alpha-defensins as candidates for the future COVID-19 therapy through molecular dynamics - Taufik Muhammad Fakih; Dwi Syah Fitra Ramadhan; Arfan Arfan (Pharmaciana, 2022)
Coronavirus 19 (COVID-19) is still a global health issue to date, SARS-CoV-2 is a novel coronavirus that is responsible for this sickness. The receptor-binding domain of the SARS-CoV-2 virus associates with angiotensin-converting enzyme 2 (ACE-2) and allows the virus to enter human cells. Natural peptides such alpha-defensin are thought to attach to the SARS-CoV-2 RBD and prohibit it from engaging with ACE-2. Molecular dynamics simulations using a computational approach are utilized to understand the stability of six alpha-defensin macromolecules using the Gromacs 2016 software. The trajectories formed are then analyzed using VMD 1.9.4 and BIOVIA Discovery Studio 2020 software. Finally, the free energy is estimated using the MM/PBSA method. The alpha-defensins 2 macromolecules were found to have the best stability based on numerous study results (trajectory visualization, RMSD, RMSF, and free energy calculations). As a result, these macromolecules could be used to build new antiviral treatments for COVID-19 infectious disease candidates.